Peramalan Exponential Smoothing Holt-winters Pada Data Jumlah Produksi Kelapa Sawit di Perkebunan Besar Swasta Provinsi Riau - Farhan Hardinata; Noor Ell Goldameir (Pelantar Press, 2024)
Palm oil is one of the largest plantation commodities in Indonesia, especially in the Riau province. The expansion of administrative coverage in palm oil companies is one of the factors affecting palm oil production. The data used in this study consists of palm oil production figures from large private estates in Riau province from January 2006 to December 2022. The methods used are the multiplicative and additive Holt-Winters Exponential Smoothing. This study aims to forecast using the multiplicative and additive Holt-Winters Exponential Smoothing models. Based on the results, the multiplicative Holt-Winters Exponential Smoothing model has a MAPE value of 13.99%, while the additive Holt-Winters Exponential Smoothing model has a MAPE value of 22.33%.